Suppressing Manganese Dissolution via Exposing Stable {111} Facets for High‐Performance Lithium‐Ion Oxide Cathode. Issue 13 (29th April 2019) - Xiao, Yao; Zhang, Xu‐Dong; Zhu, Yan‐Fang; Wang, Peng‐Fei; Yin, Ya‐Xia; Yang, Xinan; Shi, Ji‐Lei; Liu, Jian; Li, Hongliang; Guo, Xiao‐Dong; Zhong, Ben‐He; Guo, Yu‐Guo
Abstract: Spinel‐type LiMn2 O4 cathode materials commonly suffer from manganese dissolution due to the severe interfacial side reactions especially at elevated temperature. Here, a 3D hollow fusiform LiMn2 O4 cathode material is reported with preferentially exposed stable {111} facets and seamless outer structure, which is clearly confirmed by microfocused ion beam scanning electron microscopy, high‐resolution transmission electron microscopy as well as scanning transmission electron microscopy with atomic resolution. Owing to the optimal geometrical structure design and the preferentially exposed stable {111} facets, the electrode delivers excellent rate capability (107.6 mAh g −1 at 10 C), remarkable cycling stability (83.3% capacity retention after 1000 cycles at 1 C), and outstanding high‐temperature performance. Together with the analyses of electrochemical behaviors, in situ X‐ray diffraction at different temperatures, and ex situ X‐ray photoelectron spectra, the underlying working mechanism for suppressing manganese dissolution is clearly articulated. These findings could provide significant guidelines for precisely designing highly stable cathode materials for LIBs. Abstract : A 3D hollow fusiform LiMn2 O4 cathode material with preferentially exposed stable {111} facets and seamless outer structure is successfully constructed through a facile chemical‐templating route. The reasonable geometrical structure design has been demonstrated to suppress the manganese dissolution from the cathode/electrolyte interface and avoid the deposition of Mn 2+, resulting in excellent performance for lithium‐ion batteries.